2014
DOI: 10.1136/jnnp-2013-306336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deep brain stimulation of the subthalamic nucleus on freezing of gait in Parkinson's disease: a prospective controlled study

Abstract: In contrast to continued BMT, STN-DBS reduced FOG occurrence and severity at 6 months postsurgery with largely sustained effects at 12 months follow-up. Longer follow-up periods are needed to test whether FOG improvements after STN-DBS persist with disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 41 publications
6
78
0
1
Order By: Relevance
“…Previous functional imaging research pointed to a specific role of the subthalamic nucleus in gait freezers (Fling et al, 2013;Shine et al, 2013a;Vercruysse et al, 2013). Similar evidence came from clinical studies that pointed to basal ganglia outputs in terms of STN (Vercruysse et al, 2014) and the substantia nigra pars reticulata (Weiss et al, 2013) as important modulators of gait freezing. Moreover, cortical processing as well as subcortico-cortical interactions seem to be relevant.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Previous functional imaging research pointed to a specific role of the subthalamic nucleus in gait freezers (Fling et al, 2013;Shine et al, 2013a;Vercruysse et al, 2013). Similar evidence came from clinical studies that pointed to basal ganglia outputs in terms of STN (Vercruysse et al, 2014) and the substantia nigra pars reticulata (Weiss et al, 2013) as important modulators of gait freezing. Moreover, cortical processing as well as subcortico-cortical interactions seem to be relevant.…”
Section: Introductionsupporting
confidence: 54%
“…We introduced dual task interference, in order to reliably obtain freezing episodes under research laboratory conditions (Camicioli et al, 1998;O'Shea et al, 2002;Spildooren et al, 2010). StimOn was considered as therapeutic condition, as we aimed to capture ULF resistant to subthalamic stimulation therapy as a widely recognized limitation of PD state-of-the-art therapy in advanced disease stages (Krack et al, 2003;Vercruysse et al, 2014;Weiss et al, 2013). We only analyzed the ULF episodes during StimOn interference in order to study freezing resistant to subthalamic stimulation.…”
Section: Comparison Of 'Regular Tapping' and 'Upper Limb Freezing'mentioning
confidence: 99%
See 1 more Smart Citation
“…Current standard treatments such as L-Dopa and deep brain stimulation of the subthalamic nucleus (STN-DBS) often fail to control freezing behavior in the advanced disease stage (Vercruysse et al , 2014, Weiss et al , 2013. This may mirror the incomplete understanding of the complex pathophysiology behind freezing behavior.…”
Section: Introductionmentioning
confidence: 97%
“…Deep brain stimulation (DBS) has revolutionized the management of dopaminergic motor features in many patients with severe Parkinson's disease, and whilst there is some evidence in support of DBS in the treatment of gait disorders in these patients [17], its effect on the nondopaminergic motor features of Parkinson's disease, such as gait and balance, has been variable. Thus, one study showed that approximately 50% of freezers convert to nonfreezers after subthalamic nucleus DBS [18], although freezing of gait has also been shown to worsen after bilateral DBS [19]. In patients with resistant gait disturbance stimulation of the substantia nigra pars reticulata appears to improve axial motor features [20], including freezing of gait [21].…”
Section: Current Treatments For Gait Disturbancementioning
confidence: 99%